Mutation of the Phospholipase Catalytic Domain of the Pseudomonas aeruginosa Cytotoxin ExoU Abolishes Colonization Promoting Activity and Reduces Corneal Disease Severity - Tam, C. (2007)
We have previously shown that ExoU, a type III secreted cytotoxin of Pseudomonas aeruginosa, causes acute cytotoxicity towards corneal epithelial cells in vitro, and contributes to corneal disease pathology and ocular colonization in vivo. Subsequently, we reported that ExoU represses phagocyte infiltration of infected corneas in vivo. ExoU has patatin-like phospholipase activity that is required for cytotoxic activity in vitro (mammalian cell injury and death) and for disease in a murine model of pneumonia. We hypothesized that the phospholipase activity was required for ExoU-mediated corneal disease and ocular colonization. Using the murine scarification model, corneal disease pathology was examined after inoculation with ~10(6) cfu of a P. aeruginosa effector mutant (PA103ΔexoUexoT::Tc) complemented with either exoU (pUCPexoU), phospholipase-inactive exoU (pUCPexoUD344A) or a plasmid control (pUCP18). Eyes were photographed and disease severity scored at 24 and 48 h post-infection. Viable bacteria colonizing infected eyes were quantified at 6 and 48 h. Complementation with exoU caused significantly more pathology (increased disease severity scores) and enabled bacteria to better colonize (by ~1000-fold) at 48 h as compared to phospholipase-inactive exoU which did not differ from plasmid control. Surprisingly, exoU did not contribute to early (6 h) colonization. In-vitro assays confirmed that the phospholipase domain of exoU was required for cytotoxicity towards human corneal epithelial cells. Taken together these data show that the phospholipase activity of the P. aeruginosa cytotoxin, ExoU, plays a role in the pathogenesis of corneal infection via mechanism(s) occurring after initial colonization of a susceptible cornea.